Strategi Komunikasi Persuasif Guru Dalam Membentuk Karakter Murid TK Raodhatul Atfal Mutiara Hati Makassar - Fatmawati Fatmawati; Mahmud Mahmud; Musdalifah Musdalifah (Institut Nalanda, 2023)
The purpose of this research is to find out how the Teacher's Persuasive Communication Strategy in Shaping Student Character (Descriptive Qualitative Study of Teacher's Persuasive Communication Strategy in Shaping Student Character at Mutiara Hati Kindergarten Makassar. The research method used is qualitative research with a descriptive approach. This research design aims to provide abstract and general answers to questions that arise in basic research, the data collection techniques used are observation, in-depth interviews, and documentation. Data analysis was carried out using Sugiyono's version of Miles and Huberman. In this release, qualitative data analysis activities run interactively and continuously until data saturation is complete. The activities include data reduction, data display, and conclusion drawing. The results showed that the persuasive communication strategies of Mutiara Hati Raodhatul Athfal kindergarten teachers in shaping children are: Interpersonal communication where this communication is quite effective because it is done face to face, which means that the communicator (teacher) and the communicant (student) are face to face. Feedback that occurs is direct feedback. The teacher can immediately know the response given by the student. Second, dyadic communication where this communication is a communication process that takes place between two people face to face,